(untitled) (TEST Trento Student Law Review, 2021)
The paper focuses on Border Carbon Adjustment (BCA) measures and their legality vis-à-vis the World Trade Organization (WTO) law. As measures limiting international trade, border carbon adjustments can conflict with WTO law, either representing a discriminatory trade measure or a quantitative or qualitative restriction. Nonetheless, mitigation of climate change is becoming increasingly warranted, making scholars more and more concerned with solutions that allow to harmonize carbon reduction measures and international trade, being also beneficial to the international market. The paper analyses the role of BCA measures in the multilateral trade relations among states, examining which provisions of the General Agreement of Tariffs and Trade (GATT) may be incompatible with them. It also focuses on the anatomy of those incompatibilities, to investigate whether and how BCA measures could be framed in compliance with WTO law, analyzing the role of WTO case law and GATT’s exceptions on the matter.